An efficient generation method of embedded reinforcement in hexahedral elements for reinforced concrete simulations - Markou, George; Papadrakakis, Manolis (My University, 2012)
In this paper, an automatic procedure for the generation of embedded steel reinforcement inside hexahedral finite elements is presented. The automatic mapping of the entire reinforcement network inside the concrete hexahedral finite elements is performed using the end-point coordinates of the rebar reinforcement macro-elements. By introducing a geometrical constraint, this procedure decreases significantly the computational effort for generating the input data of the embedded rebar elements in three-dimensional finite-element analysis, particularly when dealing with relatively large-scale reinforced concrete models. The computational robustness and efficiency of the proposed mesh generation method are demonstrated through numerical experiments. © 2011 Elsevier Ltd. All rights reserved.
Keywords: Embedded reinforcement; Reinforced concrete; Mesh generation; Hexahedral elements; Numerical methods; Finite element method